Strategi Pembelajaran Berbasis Konflik Sosial Dalam Mengembangkan Keterampilan Berpikir Kritis Peserta Didik Pada Mata Pelajaran IPS Di SMP 1 Bandung - Silvi Nur Afifah; Nuansa Bayu Segara; Sugiantoro; Ali Imron (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
This study aims to examine the effectiveness of social conflict-based learning in enhancing students’ critical thinking skills in social studies (IPS) subjects. The research was conducted at SMPN 1 Bandung using a quasi-experimental method with a one-group pretest–posttest design. The participants consisted of 34 eighth-grade students. The research instrument was a critical thinking test that measured students’ ability to analyze, evaluate, and synthesize social issues. Pre-test results showed that 29 students demonstrated good critical thinking skills, while 5 students were categorized as very good, with an average score of 74.94. After the implementation of the social conflict-based learning model, the post-test results indicated a significant improvement: 33 students reached the very good category, and only one student remained in the good category, with the average score rising to 84.41. These findings suggest that learning based on social conflict is effective in fostering students’ critical thinking skills, encouraging them to engage with social issues in a more reflective and analytical manner.